The Green Souvenir Industry of Kerala – A Comprehensive Analysis - Robinet Jacob; Mahadevan Pand Anita T A (Atna, J Tour Stud, 2016)
Handicrafts and souvenirs have a long and glorious tradition behind them. They represent the culture of the people and from a great heritage of art. Souvenirs are a manifestation of the creative impulse of people. The specialty of the handicraft is that it reflects the craftsmanship of each and every part of the country. Souvenirs always remind a traveller of a particular place that it was purchased from. Souvenir trade improves the local economy and even serves as a brand image or icon of the destination visited by tourists while providing easy visibility. Souvenirs also help in the word of mouth marketing of a destination. The souvenir trade worldwide is part of a rich handicraft tradition that evolved over the years. India has a diversity of souvenirs, and so does Kerala. The uniqueness of Kerala isits abundance of plant or natural fibre-based souvenirs. But, little research has been done on the process of production or the potential it provides in promoting tourism. This study is an attempt to look into the problems and prospects of plant or natural fibre based - „green souvenirs‟ of Kerala and to offer suggestions for improving its market.